Optimasi Access Control List (ACL) Jaringan dalam Menangkal Akses Ilegal Jaringan Cisco - Arif, Sulthan Cendikia; Surapati, Untung; Akbar, Yuma; Hidayat, Aditya Zakaria (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study examines how to block unauthorized access while keeping services available in an enterprise network. The approach combines Access Control Lists (ACLs) allow/deny rules on routers and Policy-Based Routing (PBR), which steers specific traffic without changing the main routing setup. The object of study is a lab simulation with four understandable parts: a central network (head office), an applications/services network, a provider/carrier network, and an external network (internet/partners). The method evaluates three scenarios: baseline, ACL, and ACL + PBR, in a virtual environment using straightforward measurements (ping, traceroute, and rule/route activity logs). Results show the internal subnet is closed in both directions as required; the legitimate path from the central network to the services network remains available and balanced via the provider network; there is no route leakage from the external network to unauthorized areas; and PBR successfully guides specific flows without disrupting the primary path. In conclusion, combining ACL + PBR effectively strengthens security while maintaining service availability, serving as a practical guide for multi-domain enterprise networks.